2015
DOI: 10.3400/avd.oa.14-00133
|View full text |Cite
|
Sign up to set email alerts
|

Open Surgical Repair Can Be One Option for the Treatment of Persistent Type II Endoleak after EVAR

Abstract: Purposes: Endovascular abdominal aortic aneurysm repair (EVAR) is an increasingly used method of repairing abdominal aortic aneurysm (AAA). However, the treatment of persistent type II endoleak is still a controversial issue. Five cases are reported here in which we performed open surgical repair of growing aneurysm due to persistent type II endoleak. Method: Totally 128 EVAR cases were retrospectively reviewed, which were operated in our hospital from April 2008 to October 2013. These cases were followed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Currently there is no consensus as to the optimal treatment strategy for T2E. The indication for treatment typically includes persistent endoleak (> 6 months) and continued sac expansion (> 0.5 cm) (Yamada et al, 2015; Ozdemir et al, 2013). Frequently used strategies include: 1) transarterial embolization of the feeding vessel accessed from the superior mesenteric or internal iliac artery collaterals; and 2) embolization via direct sac puncture from a translumbar (Ozdemir et al, 2013) or transabdominal (Zener et al, 2018) approach.…”
Section: Introductionmentioning
confidence: 99%
“…Currently there is no consensus as to the optimal treatment strategy for T2E. The indication for treatment typically includes persistent endoleak (> 6 months) and continued sac expansion (> 0.5 cm) (Yamada et al, 2015; Ozdemir et al, 2013). Frequently used strategies include: 1) transarterial embolization of the feeding vessel accessed from the superior mesenteric or internal iliac artery collaterals; and 2) embolization via direct sac puncture from a translumbar (Ozdemir et al, 2013) or transabdominal (Zener et al, 2018) approach.…”
Section: Introductionmentioning
confidence: 99%
“…For typical type II endoleaks such as those of the lumbar artery and IMA, surgical ligation of the causative blood vessel and sacotomy have been highly successful. 7) If the culprit blood vessel in the present case was an anatomical variation, this approach should be effective. Conversely, if the vessel was part of the vasa vasorum, whether this treatment would be the optimal management is unclear.…”
Section: Discussionmentioning
confidence: 88%
“…50 This technique is free from incompletely treated endoleak, and this means that patients will not need subsequent interventions and periodical hospital attendings. 42 Maitrias et al 51 reported a series of 21 patients with TIIEL, with a 100% success rate treated by an open approach with stent-graft preservation. Moulakakis et al 52 also reported a 100% success rate on 22 patients treated by OSR with sacotomy and suturing of feeding vessels, with a complication rate of 13.6%.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, using CT guidance and fluoroscopy causes high radiation exposure to the patients. 42 Complications of these techniques include atrial fibrillation, myocardial infarction, pseudoaneurysm, multiple organ failure, bowel ischemia, renal artery perforation, pneumonia, sepsis, or retroperitoneal bleeding. 43 Infection of the endograft after treatment for TIIEL has also been reported.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation